(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article discusses logistics costs in agriculture and ways to reduce them. Modern approaches to logistics in the agricultural sector require a comprehensive analysis of all stages of transportation and storage of products, which directly affects economic efficiency. The paper analyzes key factors contributing to the growth of logistics costs, such as inefficient organization of transport flows, inconsistency of infrastructure with the requirements of agricultural enterprises and high costs of storing products. Possible solutions for optimizing these processes are proposed, including the introduction of information technology, improving interaction between participants in the logistics chain and modernization of infrastructure. Based on the analysis, recommendations are presented for reducing logistics costs, which will improve the competitiveness of the agricultural sector.